Exploitation of a link between antibacterial agent-resistance and biofilm-formation by classical and emergent pathogens - João, Inês (2013)
Objectives: In recent years nosocomial infections have gained growing importance. Among their etiological agents are “classical” pathogens such as S.aureus and also emergent pathogens, previously neglected, such as nontuberculous mycobacteria (MTM). The ability to resist to antibacterial agents, such as antibiotics and disinfectants, is shared by all of them. Here we aim to establish a link between bacterial virulence, antibacterial agents’ resistance and biofilm formation. Methods: Bacterial reference strains and clinical isolates were grown in adequate medium. Among the “classical” pathogens used are E.coli, K. pneumoniae, S. aureus and P. aeroginosa. The group of emergent pathogens includes M.fortuitum, M.abcessus, M.chelonae, M.avium etc. NTM susceptibility test to antibiotics was evaluated by broth based microdilution method and interpreted according to NCCLS guidelines. The desinfectant (oxygen peroxide, ammonium quaternary salts [AQS] and glutaraldehyde [GA) efficacy was performed according to the approved guidelines. The susceptibility was performed by two different methods: broth microdilution and diffusion in solid medium. In order to evaluate the effect of these agents in bacteria a scanning electron microscopy (SEM) study was performed. Biofilm forming ability was evaluated by the microtiter-plate test. The assay was performed at 25ºC and 37ºC in optimal growth media, phosphate saline buffer pH 7.4 and water during for different periods of time. Fast growing bacteria were assayed for 3 days while slow growers were assayed for 15 days.